Study of Electrical Properties of the Binary System MnO2-NaVO3 at Different Frequencies (Latakia University Journal -Basic Sciences Series, 2021)
Samples were prepared within the binary system MnO2-NaVO3 at different molar percentages depending on the ceramic method using amorphous MnO2, and crystalline NaVO3, according to (x)MnO2 -(100-x)NaVO3, for the composite ratios (x= 5, 6, 10, 20, 25, 30, 33.33, 50, 66.66, 70, 71, 75, 80, 90) and the samples were sintered at 450oC for 15 hours, and the electrical properties of the prepared samples were studied, such as the specific electrical resistivity ρ, electrical conductivity σ, electrical capacitance C, and the relative dielectric constant Ԑr, and the loss tangent tanδ within the frequency range (5Hz -1MHz), the results showed that the resistivity values ​​of all the prepared samples increased, and the higher values ​​were in the samples with an increase in the concentration of sodium metavanadate, in addition to the increase in the values ​​of electrical conductivity, and electrical capacitance, and the relative dielectric constant and the loss tangent with the increase in the content of amorphous manganese dioxide.